Results from the first science run of the ZEPLIN-III dark matter search experiment - Lebedenko,VN; Araujo,HM; Barnes,EJ; Bewick,A; Cashmore,R; Chepel,V; Currie,A; Davidge,D; Dawson,J; Durkin,T; Edwards,B; Ghag,C; et al. (Physical Review D- particles, fields, gravitation, and cosmology, 2009)
The ZEPLIN-III experiment in the Palmer Underground Laboratory at Boulby uses a 12 kg two-phasexenon time-projection chamber to search for the weakly interacting massive particles (WIMPs) that mayaccount for the dark matter of our Galaxy. The detector measures both scintillation and ionizationproduced by radiation interacting in the liquid to differentiate between the nuclear recoils expected fromWIMPs and the electron-recoil background signals down to 10 keV nuclear-recoil energy. An analysisof 847 kg days of data acquired between February 27, 2008, and May 20, 2008, has excluded a WIMPnucleonelastic scattering spin-independent cross section above 8:1 10 8 pb at 60 GeVc 2 with a 90%confidence limit. It has also demonstrated that the two-phase xenon technique is capable of betterdiscrimination between electron and nuclear recoils at low-energy than previously achieved by otherxenon-based experiments.